Thermomechanical Properties of KevlarTM Reinforced Benzoxazine-Urethane Alloys - Rimdusit S; Okhawilai M; Kasemsiri P (ASEAN Journal of Chemical Engineering, 2013)
Ballistic armor is one of an important application which required high performance of fiber-reinforced polymer due to its outstanding specific mechanical properties. Therefore, KevlarTM reinforced benzoxazine-urethane alloys as ballistic impact resistance composites were developed in this research. The polybenzoxazine alloy composites were fabricated by compression molding at 200ºC and 5 MPa by a compression molder. The amount of urethane fraction in the alloy matrix was ranging from 0-40wt% while the fiber content was kept constant at 80wt%. The mechanical properties of the matrix alloys and their KevlarTM fiber composites were characterized by dynamic mechanical analysis and universal testing machine. The results revealed that storage modulus at room temperature of the composites was reduced from 16.82 GPa when using the neat polybenzoxazine as a matrix to the value of 11.89 GPa at 40wt% of urethane content in the alloy matrix. Moreover, the more urethane in the alloy matrix resulted in lower flexural modulus of the KevlarTM composites i.e. 22 GPa when using the neat polybenzoxazine as a matrix to the value of 12 GPa when using 40wt% of urethane in the alloy matrix. Interestingly, glass transition temperature (Tg) obtained from the maximum peak of the loss modulus was observed to be in the range of 187-247ºC, which was significantly higher than those of the two parent polymers. Furthermore, the activation energy of the alloys was found to increase with increasing urethane content, which corresponded to the observed Tg value enhancement. The observed synergism in Tg of KevlarTM reinforced benzoxazine-urethane was an outstanding characteristic for a wide range of applications, which requires high thermal stability.